DIGITAL SKILLS DAN DIGITAL ETHICS : TANTANGAN DALAM PENGUMPULAN, PENGGUNAAN DAN PENYEBARAN DATA PADA GENERASI Z - Hermanto, Fredy; Lukitawati, lukki; Handoyo, Eko (Social Landscape Journal, 2024)
The speed and efficiency of the internet has made it an indispensable part of society. They can connect directly without leaving their location to people around the world through applications such as e-mail, social media or instant messaging applications. Having digital literacy skills means being able to use technology effectively to find and evaluate information, communicate with others, and create content. Without these skills, individuals can find themselves left behind in a world where so much of our personal and professional lives are conducted online. Generation Z is a generation that contributes quite high in the use of the internet in Indonesia. based on data from IDN Research Institute in collaboration with Populix from generation Z who access the internet in the range of 7-10 hours / day reaches 20.9%. This research will focus on the ability of digital skills and digital ethics in generation Z. Digital skills are skills needed to be able to live a healthy and productive digital life, and contribute to building a digital cultural environment. The emergence of hate speech, fake news, bullying, pornogoraphy, and fraud in the digital world makes it necessary to know the initial ability to use digital devices owned by users, especially generation Z so that these negative impacts can be avoided. The method used in this research is quantitative descriptive research method. This research focuses on students who represent generation Z. The factors analysed in this research include their digital skills and digital ethics. The factors analysed in this study include their digital skills and digital ethics. The data collection technique was distributed through a questionnaire. The results were then presented in the form of descriptive statistics to determine the ability of digital skills and digital ethics of Generation Z. The results of the study discuss several indicators such as the duration of accessing the internet, the use of the internet for communication, for social media, searching for information, the ability of digital skills and digital ethics including the ability to connect devices to the internet network, the ability to download applications and files, the ability to search and access data, information and digital content, the ability to check the correctness of digital information, the ability to compare information, the ability to save data, information and content, the response to share screenshots to social media, Ethics when seeing negative comments on personal posts.